Exploring the Association Between Work–Family Conflict and Job Involvement - Liu, Jianhong (International journal of offender therapy and comparative criminology, 2020)
Past research among U.S. correctional staff has found that work-family conflict has negative outcomes such as decreasing job satisfaction, decreasing organizational commitment, and increasing job stress. Little empirical research has addressed the association of the specific types of work-family conflict with job involvement. The present study contributes to the literature by separately analyzing the relationship of the four specific major types of work-family conflict (time-based conflict, strain-based conflict, behavior-based conflict, and family-on-work conflict) with job involvement among surveyed staff at two Chinese prisons. Job involvement varied by the type of work-family conflict. Specifically, time-based conflict and strain-based conflict had nonsignificant association with job involvement, but behavior-based and family-based conflicts had significant negative associations.